Fairness in Online Games and Esports in Southeast Asian Societies: An Islamic Law Perspective (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2025)
Online gaming and esports have gained significant popularity among Muslims in Southeast Asia. However, this trend has raised several concerns related to sharia issues such as gacha system, microtransactions and loot boxes. All these issues contribute to the issue of fairness in playing online games and esports. Therefore, this study aims to examine sharia ruling on fairness in online games and esports. This qualitative study applies content analysis that relates to normative Islamic legal analysis. Terms of reference have been set up as guidance, extracted from main opinion of three madhhab (Islamic law school of thoughts), namely al-Shafi’iyyah, al-Malikiyyah and al-Hanabilah according to their primary references. The modus operandi of online game and esports are identified and focused on microtransactions, gacha system and loot boxes. Interviews with esports players provides information on how these three items work. Ultimately, Islamic legal analysis determines rulings on these items related to fairness according to opinion of the aforementioned madhhab with their terms of reference. This study reveals that the loot box features and unlimited purchase in online games and esports contradict the requirement for fairness according to sharia. It provides additional guideline for sharia compliant online games and esports especially in Southeast Asia. It also suggests concrete measures such as mandatory spending caps, transparency in loot box mechanics, and certification for Sharia-compliant online games and esports.
Keywords: Fairness; Online games; Esports; Loot boxes; Microtransactions; Islamc Law